Base cations release in soils along the 127‐year Hailuogou glacial retreat chronosequence - Basdediós, Nuria; Wu, Yanhong; Wilcke, Wolfgang (Soil Science Society of America journal, 2022)
At the Hailuogou glacial retreat chronosequence, a mature forest has surprisingly fast developed in ∼120 yr, although the glacial debris is dominated by nutrient‐poor granite with a small contribution of carbonate minerals. In previous work, we hypothesized that the fast vegetation development is synchronized with initial fast carbonate weathering followed by slow silicate weathering. To test this hypothesis, we (a) characterized the composition of the glacial debris to elucidate the sources of base cations and (b) determined the base cation release kinetics from topsoils (0–10 cm) along the chronosequence with a weathering experiment at a constant pH value (pHstat). Besides granitic rocks, the glacial debris contained some meta‐sedimentary and meta‐volcanic calc‐silicate rocks, amphibolite, mica schist, and quartzite. Although the total Ca concentration of the glacial debris was only about double that of Mg, K, and Na, during the 1st day of the pHstat experiment, the released mass of Ca was >10 times higher than that of Mg and K, and even about 100 times higher than that of Na. The size of the fast‐reacting Ca‐carbonate pool decreased quickly in the first approximately 40 yr, after which a slow‐reacting Ca‐silicate pool matched the fast‐reacting pool with a size of 1.9 ± 0.6 g kg–1 Ca. In contrast, for Mg, K, and Na the slow‐reacting pool dominated from the beginning, suggesting that these elements mainly originated from silicate weathering. Our findings support the view that the well‐synchronized interplay between carbonate and silicate weathering facilitated the fast vegetation succession. Core Ideas Calcite occurred in the mainly granitic substrate of the Hailuogou chronosequence. The calcite originated from meta‐sedimentary and meta‐volcanic rocks in the glacial debris. Carbonate weathering determined the rapid initial Ca but not Mg release. The main sources of weathered Mg, K, and Na were silicate minerals. Base cation release kinetics followed the order, Ca>>Mg>K>>Na.